Factors associated with adherence to physical activity guidelines in patients with prostate cancer. Issue 11 (7th June 2013) - Chipperfield, Kelly; Fletcher, Jane; Millar, Jeremy; Brooker, Joanne; Smith, Robin; Frydenberg, Mark; Oh, Tracy; Burney, Sue
Abstract: Objective: This study aimed to estimate the proportion of patients with prostate cancer (PCa) meeting the National Physical Activity Guidelines of Australia (NPAGA) and determine sociodemographic and medical factors associated with meeting these guidelines. Secondary aims included examining physical activity (PA) levels by treatment type and domain (leisure, work, transport and domestic) and establishing a predictive model of the likelihood that men with PCa would meet NPAGA. Methods: A questionnaire was mailed to 638 men with PCa attending for treatment at the Alfred, Cabrini or Latrobe Regional Hospitals during 2010 and 2011, with a response rate of 59%. Measures included International Physical Activity Questionnaire, Hospital Anxiety and Depression Scale, Functional Assessment of Cancer Therapy – Prostate and sociodemographic items. Inclusion criteria were English speaking men aged 40 to 80 years, who had undergone radiotherapy (RT) between 9 and 30 months prior to the survey. Results: Of 356 men with PCa, less than half were meeting NPAGA (41.9%). Lower education and quality of life (QoL), a higher number of comorbid conditions and symptoms of depression and anxiety were associated with decreased leisure‐time PA. Patients treated with androgen deprivation therapy were significantly less active than patients treated with RT only. Logistic regression analyses indicated that the likelihood of meeting NPAGA was significantly lower with higher levels of depressive symptoms and lower levels of education. Conclusions: Meeting NPAGA is associated with higher QoL and psychosocial well‐being in men with PCa. These findings contribute important information for targeting PA interventions to PCa survivors. Copyright © 2013 John Wiley & Sons, Ltd.